ANALISIS EFEKTIVITAS DAN POTENSI RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KOTA BANJARMASIN - SITI AMALIA (PPJP Universitas Lambung Mangkurat, 2018)
This study aims to find out how the potential of regional levies in the city of Banjarmasin through the rate of growth and contribution by using a potential matrix, how is contribution of acceptance of regional retribution to increase of original regional incomein Banjarmasin City and how effectiveness level of attainment of local retribution levies in Banjarmasin City during 2012-2016. The results of the study using the potential matrix to see the potential of regional levies through growth rates and these contributionsshows the average yield of positive growth rate and its contribution is not potential, these results indicate that the potential of regional levies in Banjarmasin City during 2012-2016 fall into the developing category.While the level of effectiveness of local retribution into the category very effective because the average value of effectiveness of regional levies during the last five years is above 100%. Keywords:local retribution, original regional income, effectiveness, potential matrix, growth, contribution.